Inovasi Pembelajaran Pendidikan Agama Islam (PAI) Berbasis HOTS dan Moderasi Beragama - Surdi Pabbe; Akhyarur Rijal (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Higher-Order Thinking Skills (HOTS) and Religious Moderation are efforts to improve the quality of the learning process and outcomes of students in the digital era. This approach emphasizes the importance of higher-order thinking abilities—including analysis, evaluation, and creation—as well as the development of a balanced and tolerant religious attitude. Through a literature review, this study examines various academic references related to the implementation of HOTS and Religious Moderation in Islamic Religious Education (PAI), including supportive learning models, challenges encountered, and strategies to address them. The results indicate that integrating HOTS and Religious Moderation can create more contextual, critical, and meaningful PAI learning. Students not only understand Islamic teachings theoretically but are also able to analyze religious phenomena deeply and apply them in daily life with a moderate attitude. Furthermore, this innovative learning approach is considered effective in fostering a generation that is critical of information, tolerant of differences, and capable of maintaining social harmony. Overall, the application of PAI learning based on HOTS and Religious Moderation makes a significant contribution to developing students’ intellectual, moral, and social intelligence. This learning model is not only relevant in the context of Islamic education but also strategic for building a peaceful, inclusive, and principled national character in line with the concept of rahmatan lil ‘alamin.